2014
DOI: 10.1152/physiolgenomics.00152.2013
|View full text |Cite
|
Sign up to set email alerts
|

Basal microRNA expression patterns in reward circuitry of selectively bred high-responder and low-responder rats vary by brain region and genotype

Abstract: Hamilton DE, Cooke CL, Carter BS, Akil H, Watson SJ, Thompson RC. Basal microRNA expression patterns in reward circuitry of selectively bred high-responder and low-responder rats vary by brain region and genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(51 reference statements)
1
2
0
3
Order By: Relevance
“…The current findings are supported by the results of Thompson and colleagues that demonstrated differences in microRNA expression between animals classified as high or low responders in their processing of reward and anxiety (Hamilton et al, 2014). In addition to the mPFC, microRNA regulation in the nucleus accumbens is important in mediating resilience to stress (Dias et al, 2014).…”
Section: Rj Chen 15supporting
confidence: 82%
“…The current findings are supported by the results of Thompson and colleagues that demonstrated differences in microRNA expression between animals classified as high or low responders in their processing of reward and anxiety (Hamilton et al, 2014). In addition to the mPFC, microRNA regulation in the nucleus accumbens is important in mediating resilience to stress (Dias et al, 2014).…”
Section: Rj Chen 15supporting
confidence: 82%
“… 24 , 25 It has been demonstrated that brain-specific miRNA candidates within the amygdala regulate anxiety and fear-related behaviours in mice. 26 , 27 , 28 However, there is a paucity of information about whether the microbiome could regulate amygdala-dependent fear behaviours or modify the expression of miRNAs in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Следует отметить, что последовательности предшественников ортологичных микроРНК собаки и лисы в основном идентичны. Мы ожидали увидеть разницу в уровнях экспрессии микроРНК в гиппокампе у двух групп лисиц, отличающихся по стресс-ответу, агрессии и тревожности, так как микроРНК-регуляция затрагивает ряд генов, участвующих в этих реакциях в разных структурах мозга (Hamilton et al, 2014;Hollins, Cairns, 2016). Исследование базального уровня микроРНК у двунаправленно селекционируемых групп крыс (bHR и bLR), отличающихся по подобным же признакам, показало достоверные различия между группами в nucleus accumbens и prelimbic cortex.…”
Section: Discussionunclassified
“…D.E. Hamilton с коллегами предполагают наличие подобных различий в профиле микроРНК также в гиппокампе и миндалине (Hamilton et al, 2014). Однако в нашем исследовании не выявлено значимой разницы в экспрессии не только у микроРНК, ортологи которой, по данным литературы, изменяют экспрессию при разных формах стресса (Hollins, Cairns, 2016) Приложение 2, но и у остальных обнаруженных микроРНК.…”
Section: Discussionunclassified
See 1 more Smart Citation